Decades not Lost, but Won: Increased Employment, Higher Wages, and More Equal Opportunities in the Japanese Labour Market. - BLIND, Georg D.; LOTTANTI VON MANDACH, Stefania (Social Science Japan Journal)
We take a fresh analytical look at the developments in the Japanese labour market over the last two decades and provide answers to three key questions: first, was regular employment replaced by non-regular employment on an aggregate level in general and at the expense of younger generations in particular? Second, how do today's labour market outcomes compare to the heydays of the Japanese economy, i.e. to the late 1980s? Third, have wage gaps between men and women as well as between regular and non-regular employees increased, stayed the same, or shrunk? Contrary to both public perception and many research opinions, we find that the Japanese labour market as a whole has produced normatively positive outcomes of an unexpected magnitude in a long-term perspective. By 2010, employment has expanded beyond the structural frame of 1988 both in its non-standard and in its standard segment. We further find that the increase in non-regular employment was predominantly due to an increase in labour demand, mirrored by a significantly narrowed wage gap between non-standard and standard employment. Lastly, we find that women have made substantial inroads into the labour market, both in terms of regular employment and real wage development.